Evaluacion del proceso de obtencion de nectar a partir de jackfuit (Artocarpus heterophyllus) en el canton quevedo,provincia de los rios - Cedeño Zambrano, Vanesa (2011)
This research work: "EVALUATION PROCESS FOR OBTAINING FROM NECTAR JACKFRUIT (Artocarpus heterophyllus) IN THE CANTON QUEVEDO, LOS RIOS PROVINCE" was made considering the necessity of allowing agribusiness development alternatives while industrialization. The Artocarpus heterophyllus is commonly referred as the Jaca, being native to the tropical regions of South America was one of the first American fruit trees introduced to the Old World. In Ecuador, jackfruit cultivation is an interesting option for agricultural diversification and the development of agro-industrial processes. Since the rich biodiversity provides to humanity of new crops in a wide variety of industrial and medical products. Usually the harvesting procedure is a problem, immature fruit maturity or those past (even with insect attack) from the mixture of varieties, not having a good selection of fruit. Based research was to identify problems crop management, manufacturing, marketing and later use. Process is warranted and completion of the investigation and that is looking for improvements of this product with the requirements of a new consumer market. The variables evaluated were: • pH • Acidity • Brix • Microbiological analysis • Pulp suspended • Humidity To evaluate the production of nectar was performed 24 trataminetos Jackfruit, the same that resulted from three factors combine study with their respective levels in a factorial arrangement of AxBxC.